IMPLEMENTASI PENGENALAN FINGER VEIN PADA SISTEM PEMBAYARAN MENGGUNAKAN METODE LLBPh - Dewi Hastuti; Ika Purwanti Ningrum; Adha Mashur Sajiah; Jayanti Yusmah Sari (Informatics Engineering Department of Halu Oleo University, 2018)
Payment is one of the important activities that in the transaction process. Currently, technology that supports payment system is quite a lot, however in implementation technology used still has a various of a problem such as, pin code used can be stolen, duplicated, and didn't possibility someone can forge wt the pin code of the plastic card owned. One way that can be used to resolve this is identification by taking the unique characteristics of limb.Finger vein is one of the biometric images that can be used to recognize a person. Finger vein can be used as an effective, efficient, and economical tool of payment the role of plastic cards. In this research, the method used is Local Line Binary Pattern horizontal (LLBPh). This method has a good ability to recognize of patterns, can resolve the shading irregular image and the image area that has a high saturation. Based on the experimental results that used, the LLBPh method produces an accuracy of 92.08 with the threshold value.Keywords—Finger Vein recognition, LLBPh, Payment